Diuron exposure induces systemic and organ-specific toxicity following acute and sub-chronic exposure in male Wistar rats - Domingues, Alexandre [UNESP]; Barbisan, Luis Fernando [UNESP]; Martins, Priscila Raquel [UNESP]; Tozzi Spinardi-Barbisan, Ana Lucia [UNESP] (Elsevier B.V., 2011)
Diuron [3-(3,4-dichloropheny1)-1,1-dimethylurea] is a substitute urea herbicide widely used on agricultural crops with potential mutagenic, teratogenic, reproductive and carcinogenic effects. Nonetheless, its toxic potential on the immune system needs a detailed assessment. Thus, in order to evaluate the adverse effect of this herbicide on lymphohematopoietic organs and macrophage activity, male Wistar rats were orally treated with Diuron at 125, 1250 and 2500 ppm for 14, 28 or 90 days. General signs of toxicity were observed in Diuron-treated groups (1250 and 2500 ppm), including reduced food intake and body weight gain, as well as higher relative weights for spleen, kidneys and liver (28 and 90-day toxicity studies) and elevated serum levels of ALT, albumin, total protein, creatinine and urea (28-day toxicity study). Diuron exposure caused a severe depletion of splenic white pulp compartments and cellularity, followed by a decreased number of CD4(+) T lymphocytes, increased extramedullary hematopoiesis and deposition of hemosiderin in red pulp. Despite alteration in macrophage spreading, the macrophagic activity was not significantly affected by the herbicide. Under these experimental conditions, the results suggest that Diuron exerts systemic and target-organ toxicity, mainly at higher concentration. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Diuron; Toxicity; Rat; Peritoneal macrophages; Lymphoid organs